A Case of Crossed Left Renal Ectopia Identified during Colostomy Reversal - NeMoyer, Rachel (Case Rep Surg, 2017)
Unilateral crossed renal ectopia without fusion is an uncommon anatomic anomaly, which often goes undiagnosed. We report a case of this renal variant discovered incidentally during colostomy reversal after Hartmann's procedure for diverticular stricture.